Review on Late Pleistocene‐Holocene relative sea‐level changes in Kuwait: New evidence from Failaka island. (2nd March 2021) - Arhan, Damien; Pavlopoulos, Kosmas; Fouache, Éric
Abstract: New results from fieldwork carried out on Failaka island testify to relative sea‐level fluctuations during Late Pleistocene and Holocene. This study is based on analysing, sampling and dating geomorphological sea‐level indicators, including beach ridges or beachrocks. The results have been compared and harmonised with recalibrated data from pre‐existing literature to reconstruct the relative sea‐level local chronology. The vertical displacement identified may have induced coastline mobility and significant environmental changes and impacted the human occupation in Failaka and along the coastal areas of Kuwait. Eventually, the results highlight the impact of large‐scale crustal deformations on regional relative sea‐level variations.